The effectiveness of positive thinking on academic self-concept and exam anxiety of high school students in Zahedan - Hossien Jenaabadi; Masoud Salarpoor (مطالعات روانشناسی تربیتی, 2021)
The aim of this study is to investigate the effectiveness of positive thinking training on academic self-concept and test anxiety of high school students of Zahedan. The research method was quasi-experimental pre –test and post -test. The statistical population of this study includes high school students studying in Zahedan in the year 1398-99, in which 30 subjects were selected voluntarily and purposefully and then they divided into two experimental and control groups. The research tools are the academic self-concept (Yesen, Chen, 2004) and the exam anxiety questionnaire (Fridman and Bendas- Jakoob, 1997). The validity of this research was content and reliability was estimated using Cronbach's alpha coefficient for the self-concept questionnaire of 0.92 and test anxiety questionnaire of 0.90. For statistical analysis of data from frequency, percentage, mean and standard deviation and also for testing research questions from single sample t test, univariate analysis of covariance and multivariate analysis of covariance using SPSS-25 software, statistical analysis was performed on the data. The results demonstrated that positive thinking training is effective on test anxiety and its components in high school students of Zahedan. Furthermore, teaching positive thinking has been effective on academic self-concept and its components in high school students of Zahedan. The results of one-sample t-test also indicated that the rate and level of test anxiety and self-concept of high school students of Zahedan is at a desirable level.